PENGARUH MODEL SETS TERHADAP KETERAMPILAN PENGAMBILAN KEPUTUSAN SISWA SMP TOPIK PENCEMARAN LINGKUNGAN - Fitri Rahmadanti; Hairida Hairida (Jurnal Ilmiah Ar-Razi, 2020)
This study aims to determine the effect of the SETS learing model (Science, Environement, Technology, and Society) on the decision-making skills of students of SMP Negeri 01 Belitang on environmental pollution material. The form of research used was a quasi experimental design with are search nonequivalent control group design. The sample of this research is class VII A as a control class amounting to 25 students and class VII B as an experimental class totaling 25 students, using saturated sampling technique. Data calculation techniques are measurement and interview techniques. Based on the analysis using the U-Mann Whitney test ( which shows the differences in the decision-making skills of students who were given the SETS learning model and given conventional learning model. The effect size value obtained is 1,3 with high criteria and has an effect of 90 % on improving decision-making skills.